2014
DOI: 10.1167/iovs.14-13897
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-1 Suppresses Choroidal Neovascularization and Vascular Leakage

Abstract: Ang1 supplementation can be established as a therapeutic strategy to suppress the CNV formation and vascular leakage by inhibiting the recruitment of angiogenic macrophages and tightening the endothelial junctions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 37 publications
3
45
0
Order By: Relevance
“…26 Angiopoietin 2 is upregulated by hypoxia and has been detected in surgically removed human CNV membranes. 27 Single and combined inhibition of angiopoietin 2 and VEGF-A are showing promising results in the management of ocular angiogenesis. 28 Endothelin 1 is considered a potent endogenous vasoconstrictor in small vessels, has an important regulatory role for retinal blood flow, and also may induce angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…26 Angiopoietin 2 is upregulated by hypoxia and has been detected in surgically removed human CNV membranes. 27 Single and combined inhibition of angiopoietin 2 and VEGF-A are showing promising results in the management of ocular angiogenesis. 28 Endothelin 1 is considered a potent endogenous vasoconstrictor in small vessels, has an important regulatory role for retinal blood flow, and also may induce angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Inducible ubiquitous or photoreceptor restricted expression of Ang2 or VEGF demonstrated that Ang2 stimulated retinal neovascularization (NV) in concert with VEGF, but induced vessel regression when VEGF level was low [113]. In contrast, transgenic expression of Ang1 prevented VEGF-induced NV and exudative retinal detachment in VEGF/tet/opsin mice, but did not affect established retinal and choroidal NV [114116]. Thus, ectopic Ang1 makes ECs less responsive to VEGF-induced signals, whereas the sensitivity of ocular vasculature to Ang2 is determined by the VEGF/Ang2 ratio and additional factors, which may include integrins and ECM components [117].…”
Section: Ang–tie System In Vascular Diseasesmentioning
confidence: 99%
“…Laboratory studies largely deliver fluorescein via subcutaneous or intraperitoneal injection to identify blood-retinal-barrier compromise [13], [15], [32], [33]. Whilst this is an easy method of dye administration, it provides limited temporal information.…”
Section: Discussionmentioning
confidence: 99%